Поширення Pulsatilla grandis Wend. (Ranunculaceae) в Україні - Горбняк, Л.Т. (Український ботанічний журнал, 2012)
Описаны результаты обработки гербариев, литературных источников и собственных иссле- дований с целью уточнения географического распространения Pulsatilla grandis Wender. на территории Украины. Results of the examination of herbarium specimens, published sources and personal research data are provided in order to clarify geographic distribution of Pulsatilla grandis Wender. in Ukraine.